13.6k views
20 votes
2(x+5)=1/2(x-4)
Step by step

User Snuffy
by
5.0k points

2 Answers

2 votes


\huge\bf \underline{Solution:-}


2(x + 5) = (1)/(2) (x - 4)


⇒2x + 10 = (x)/(2) - (4)/(2)


⇒2x - (x)/(2) = - (4)/(2) - 10


⇒ (4x - x)/(2) = - 2 - 10


⇒ (3x)/(2) = - 12


⇒3x = - 24


⇒x = - ( 24)/(3)


⇒x = - 8


\\


\sf \underline{Now, \: we \: are \: gonna \: do \: correction \: test :-}


L.H.S. = 2 (x + 5)


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2( - 8 + 5)


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2 * ( - 3)


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = - 6


R.H.S = (1)/(2) (x - 4)


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (1)/(2) ( - 8 - 4)


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (1)/(2) * ( - 12)


\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = - 6


\bold{ \therefore{L.H.S = R.H.S}}


\sf \red{Hence, \: the \: value \: of \: x \: is \: - 8. }

User Alex Correia
by
4.8k points
11 votes


\text {Hello! Let's Solve this Problem!}


\text {\underline {The First Step is to Simplify}}


\text {2*x=2x}\\\text {2*5=10}\\\text {1/2*x=1/2x}\\\text {1/2*-4=-2}


\text {Your New Problem Is: 2x+10=1/2x-2}


\text {\underline {The Next Step is to Subtract 1/2x}}


\text {2x+10-1/2x=1/2x-2-1/2x}


\text {Your New Problem Is: 3/2x+10=-2}


\text {\underline {The Next Step is to Subtract 10}}


\text {3/2x+10-10=-2-10}


\text {Your Final Problem Is: 3/2x-12}


\text {\underline {The Final Step is to Multiply 2/3}}


\text {2/3*3/2x=2/3*-12}


\text {Your Answer Would Be:}


\Huge\boxed {x=-8}


\text {Best of Luck!}

User Elvin Jafarov
by
4.9k points